Comparisons of the results from between Rapid Entire Body Assessment and Quick Exposure Check as ergonomic evaluation tools - Pinyowiwat, Khongrit; Supapong, Soontorn; Rattananupong, Thanapoom (Chulalongkorn Medical Journal, 2020)
Background: Ergonomic tools are used to conduct risk assessments in the workplace. The Rapid Entire Body Assessment (REBA) is a favourite tool of ergonomists and practitioners, whereas the Quick Exposure Check (QEC) is more widely used. However, comparative studies of these two ergonomic tools are limited. Objectives: To compare the results of two ergonomic evaluation tools, the Rapid Entire Body Assessment (REBA) and the Quick Exposure Check (QEC), and determine the prevalence of musculoskeletal disorders using Nordic questionnaire in a steel factory. Methods: This cross-sectional study recruited 296 workers in a steel factory. The data were collected using selfadministered questionnaires and data collection forms administered by the researchers. Proportionally stratified random sampling was used. The weighted kappa coefficient was used to compare the results of the two tools. Results: The comparisons of the REBA and QEC results showed slight to fair strength of agreement. The 12- month prevalence of musculoskeletal disorders in the workers was 69.0%, and in 55.0% of those workers, their symptoms affected their work. The highest prevalence of symptoms was in the low back, followed by the shoulder and neck. Conclusion: The comparisons of the REBA and QEC results showed slight to fair strength of agreement. However, this research was conducted in only one steel factory; therefore, further studies are required.